ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode Tahun 2011â2012) - Purwanto, 11.05.52.0175; ., Wardjono (Students Journal of Accounting and Banking, 2015)
This study aims to determine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Current Ratio (CR), Price to Book Value (PBV) and Total Asset Turnover (TATO) to Return stock company belonging to the category of businesses and services listed in Indonesia Stock Exchange (IDX). The object of this research is all manufacturing companies listed on the Stock Exchange Indonesi the period 2011-2012. Determination sample with purposing sampling method is based on the availability of data during the study period and the type of data is secondary data, while the analisia method used in this study is a multiple linear regression model. The results of this study indicate that each variable has a different effects ie ROA gave the positive and significant impact on stock returns, DER and PBV negatively and significantly, while the EPS, CR and TATO with the same give and no significant positive effect on stock returns. Conclusion. This study shows that the regression model is formed by the independent variables consisting of ROA, DER, EPS, CR, PBV and TATO can be used to predict stock returns in manufacturing companies listed in Indonesia Stock Exchange (IDX).Keywords: Stock Return, Return On Assets, Debt to Equity Ratio, Earnings Per Share, Current Ratio, Price to Book Value, Total Asset Turnover